FREQUENCY OF SKIN MANIFESTATIONS IN PATIENTS ON CHEMOTHERAPY - ULLAH, MA; SAEED, M; RAFIQUE, S (Biological and Clinical Sciences Research Journal, 2023)
The study's objective was to determine the frequency of skin manifestations in patients on chemotherapy. This cross-sectional study was conducted on 170 patients on chemotherapy with post-acne scarring and hyperpigmentation not responsive to other treatments were included at the Department of Dermatology, Unit-1, Jinnah Hospital Lahore from April 2016 to September 2016. Patients of both genders and any age and on chemotherapy, at least after their first dosage, were included. Patients having skin manifestation before chemotherapy, patients with a history of HCV, those having diabetes mellitus (Fasting BSR > 100 mg/dl), and patients having other connective tissue diseases, SLE, DLE, etc., were excluded. A dermatologic examination was performed, and biopsy, mycological and bacteriological tests were conducted if necessary. Skin manifestations were labelled. A total of 170 chemotherapy patients participated in this trial. There were 58 (34.1 percent) females and 112 (65.9%) males. Fifty-three people (31.2%) had no skin manifestations, 61 people (34.9%) had one, 40 people (23.5%) had two, and 16 people (9.4%) had three skin manifestations. A total of 75 patients (44.1%) are under the age of 30, 40 patients (23.5%) are between the ages of 31 and 45, and 55 patients (32.4%) are over the age of 45. In 2 cases, acral erythema was seen (1.2 percent ). In 21 cases, dry skin was seen (12.4 percent ). There was alopecia in 93 individuals (54.7 percent ). Sixteen patients still had the eruption (9.4 percent ). Three of the patients had acne (1.8 percent ). In 7 cases, purpura was present (4.1 percent ). In 47 cases, mucositis was found (27.6 percent ). Age and gender had no impact on the number of cutaneous manifestations. People receiving chemotherapy frequently get cutaneous symptoms. Alopecia, mucositis, and xerosis were among the most typical cutaneous signs.